Cover Feature: Electrochemical Flash Fluorination and Radiofluorination (ChemElectroChem 22/2018). Issue 22 (12th October 2018) - Balandeh, Mehrdad; Rios, Alejandra; Allison, Nathanael; Shirazi, Daniela; Gomez, Adrian; Rambaran, Laura; Holloway, Travis; Sadeghi, Saman
Abstract : The Cover Feature illustrates radio‐labelling using a cation pool technique. This method provides a truly late‐stage fluorination reaction, maximizing radiochemical yield by minimizing decay through rapid reaction of the previously prepared cations with [ 18 F] fluoride. More information can be found in the Communication by M. Balandeh et al. onpage 3353 in Issue 22, 2018 (DOI:10.1002/celc.201800973 ).